Development of a VR Metaverse System for Campus Navigation Using the Dijkstra Algorithm: Pengembangan Sistem Metaverse VR untuk Navigasi Kampus Menggunakan Algoritma Dijkstra - Mochammad Nur Fikri Denintyo Denintyo; Tito Sugiharto; Yulyanto (FKOM UNIKU, 2026)
Advancements in Virtual Reality (VR) and Metaverse technologies have created new opportunities to enhance user experiences, particularly in education. This study presents the design and development of a VR-based Metaverse application for the Faculty of Computer Science at Universitas Kuningan. The application functions as an interactive promotional tool and campus navigation aid, utilizing the Dijkstra algorithm to compute the shortest routes within the virtual environment. Key features include realistic 3D campus visualizations, integrated information on essential locations, and route optimization from the main gate to user-selected destinations. Testing was conducted through black-box, white-box, and User Acceptance Testing (UAT) methods. User feedback indicated that navigation was effective, with directional clarity and usability scored at 3.59 and 3.18, respectively, while the 3D visualization received scores above 3.4 for realism. Interactivity and immersion achieved a score of 3.35, and the interface was deemed intuitive and accessible across devices (3.38 and 3.82). Despite minor issues with system responsiveness (averaging 2.65), users expressed high overall satisfaction and a strong intention to reuse and recommend the application, with a recommendation score of 3.76. This implementation highlights the potential of Metaverse technology in education and serves as a foundation for its wider adoption in Indonesian higher education